1999
DOI: 10.1016/s1359-6454(99)00312-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of adhesion in contact fatigue

Abstract: AbstractÐBy incorporating the eects of interfacial adhesion in the mechanics of rounded contact between two bodies, a new approach is proposed for the quantitative analysis of a wide variety of contact fatigue situations involving cyclic normal, tangential or torsional loading. In this method, conditions of``strong'' and``weak'' adhesion are identi®ed by relating contact mechanics and fracture mechanics theories. Invoking the notion that for strong and weak adhesive contact, a square-root stress singularity ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…In fretting fatigue there is contact between two surfaces, where small, oscillatory sliding displacements occur between the surfaces while one or both of the contacting surfaces could be subjected to fluctuating stresses. Considerable oxidation can occur in the presence of aggressive environments to cause wear and material removal at the fretted surface [125,126]. The problem of fretting is it increases tensile and shear stresses at the contact surface and generates flaws, which lead to premature crack nucleation [127].…”
Section: Fretting Fatigue Resistancementioning
confidence: 99%
“…In fretting fatigue there is contact between two surfaces, where small, oscillatory sliding displacements occur between the surfaces while one or both of the contacting surfaces could be subjected to fluctuating stresses. Considerable oxidation can occur in the presence of aggressive environments to cause wear and material removal at the fretted surface [125,126]. The problem of fretting is it increases tensile and shear stresses at the contact surface and generates flaws, which lead to premature crack nucleation [127].…”
Section: Fretting Fatigue Resistancementioning
confidence: 99%
“…Contact fatigue, such as that induced by cyclic loading of an indenter into the surface of a material, has also been used because of its perceived relevance for the study of wear processes. The indentation causes tensile stresses at the contact edges, which can lead to crack formation (Gioannakopoulos et al, 1999). This technique has been used with ceramic materials, where it is found that the damage mode depends on material microstructure; in homogeneous ceramics, a cone-shaped crack (Hertz crack) emanating from the circle of contact can ensue, while in heterogeneous ceramics, a diffuse damage zone driven by shear stresses forms underneath the indenter (Kim et al, 1999).…”
Section: Iia) Inorganic Glasses and Ceramicsmentioning
confidence: 99%
“…As an alternative to the above-described techniques based on the Rooke-Jones formula, the approach [36,37] based on analogy between the stress field in a half-plane close to the edge of flat rigid punch (Fig. 5a) and that at the tip of a crack growing from a V-notch ( Fig.…”
Section: The Basic Calculation Formulas and Analogiesmentioning
confidence: 99%
“…For comparative analysis of the Otsuka and Richard criteria applicability to the materials under study, we'll use one coordination system for assessment the crack deviation angle and therefore transform the respective criterial dependences (14)-(17) from the coordinate system (13) to system (4). This allows one to use the advantages of the approach [36,37] and to apply formulas (2) for unambiguous calculation of the global parameters K I and K II in a fictitious crack at the contact boundary, whereas the ratio K K II I is equal to the friction coefficient m. Thus, the initial crack direction will coincide with the contact surface, i.e., q j = . Then formulas (16) and (17) will be re-arranged in the coordinate system (4) in the following way:…”
Section: Account Of Multi-stage Fretting Fatigue Behavior and Use Of mentioning
confidence: 99%